Students' perception and motivation in learning mathematics and science in English / Siti Mariam Abd Aziz - Abd Aziz, Siti Mariam (2008)
This is an exploratory study that investigates the opinions of Form Four Science students in rural and urban secondary schools in Selangor on the use of English as the medium of instruction for critical subjects such as mathematics and science. A 3-part questionnaire was distributed among form four students in four different schools: 2 urban and 2 rural. Data were descriptively analysed using SPSS 12.0.The findings showed that a large majority of urban and rural secondary school students supported the policy, and wanted it to continue, as they positively perceived and preferred, English, as the medium of instruction in the teaching of critical subjects such as mathematics and science. They were ready and motivated to learn both subjects in English as it helped them improve their performance in the English language through communication with their peers and teachers. However, they faced several challenges, namely, lack of understanding, linguistic skills, available resources and stiff competitiorfto get better grades.